The Estimation of Economic Appearance and Profitability Function of Drip Irrigation in Tidal Lands (A Case of Chili Farming) - Dessy Adriani; Maryanah Hamzah; Muammar Adi Prasetya (Program Pascasarjana Universitas Sriwijaya, 2019)
The purpose of this research are (1) to determine economic appearance and (2) to estimate the profit function of the application of drip irrigation technology for chili farming in tidal lands. This research used survey method at Budi Mulya Village Air Kumbang Sub-district Banyuasin Regency. Collecting data was held on March and April of 2018. Sampling method was proportionate stratified random. Watering and fertilization of chili farming with utilizing drip irrigation technology was done by using water pump machine. Drip irrigation affected positive impact for increasing of chili farming profit. Drip irrigation technology in chili farming is more efficient than chili farming without drip irrigation technology. Economic of scales of drip irrigation technology in chili farming is 2.547, that means in increasing returns to scale condition. Farmers need government policy in applying this technology like a subsidy or loan from government.